Factors Related to Community Behaviors in Rural Area in Preventing The Covid-19 - Juradi, Nurul Wahyuni; Arman, Arman; Jafar, Nurhaedar (Journal of Aafiyah Health Research (JAHR), 2021)
Background: Coronavirus Disease 2019 or Covid-19 is a new disease that can cause respiratory problems and pneumonia. This disease caused by infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Based on the visible symptoms, Covid-19 infection can interfere with acute breathing, such as fever, cough, and shortness of breath. The average incubation period is 5-6 days, with the most extended incubation period being 14 days. Aim: To find out the factors related to community behavior in preventing the Covid-19 pandemic. Method: The research method is a quantitative method with cross -sectional study approach. The research location is in Baebunta District, North Luwu, and the research time is in February-August 2021. Data collection by distributing questionnaires with a sample of 395 people. Data analysis using chi-square test through SPSS Version 23. Results: The results of the study show that there is a relationship between gender and Education regarding the behavior of each community with P-value = 0.017 < 0.05 and Pvalue = 0.011 < 0.05 while employment, knowledge, and government policies have no significant value with P-Value respectively 0.374, 0.993 and 0.957 > 0.05. Conclusion: Education and gender have correlation on people's behavior, while, occupation, knowledge, and government policies were not.